Laparoscopic Transabdominal Preperitoneal Technique for Inguinal Hernia Repair in Adults - Thanh Xuan, Nguyen (Cureus, 2020)
Background Inguinal hernia repair is one of the most commonly performed operations in general surgery, especially in the digestive field. Since the introduction of laparoscopic repair as well as using a synthetic mesh, the surgical trends have changed in the last decade in treating inguinal hernias. The laparoscopic transabdominal preperitoneal gives a better view of the inguinal anatomy, and the procedure also has a short learning curve. We aim to evaluate the safety and early outcome of the laparoscopic transabdominal preperitoneal technique for inguinal hernia repair using a Prolene(®) mesh (Ethicon Somerville, NJ, USA). Methods A prospective study was carried out among 31 adult patients with 34 inguinal hernia cases. They underwent the laparoscopic transabdominal preperitoneal technique with a Prolene mesh at the Hue Central Hospital from December 2018 through May 2019. Results The mean age was 60.4 ± 11.8, and 96.8% of cases were male. Strangulated hernia and incarcerated hernia accounted for 2.9% and 8.8% of cases, respectively. The mean duration of unilateral inguinal hernia repair and bilateral inguinal repair was 57.1 ± 17.3 minutes and 80.3 ± 10.6 minutes, respectively. The mean duration of the postoperative hospital stay was 3.9 ± 1.4 days. One (3.2%) case with contralateral inguinal hernia was detected intraoperatively. An early and three-month postoperative evaluation showed that 93.5% and 96.8% of cases were categorized as “very good”, respectively. At the three-month evaluation, one case was reported with sensation disorder of the inguinal area, and there was no recurrence. Conclusions Laparoscopic transabdominal preperitoneal inguinal hernia repair is a safe and feasible technique. It allows surgeons to explore the opposite site and resolve the combined peritoneal diseases.